Recovery as a Gift of Blackness: Epistemic Justice in Community Engagement and Learning - Lin, James B.; Femi, Isoke N.; Lin, Barbara; Mark, Lillian (Experiential Learning and Teaching in Higher Education, 2022)
None provided